Peningkatan kemampuan sains anak melalui metode eksperimen penggunaan tepung sagu - Romi Narti (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
This research uses Classroom Action Research conducted in Pertiwi Kajai Kindergarten. This research was conducted for 2 months, namely as many as 2 cycles, namely cycle I consisted of 3 meetings and cycle II consisted of 3 meetings. Data collection with observations, interviews, and documentation were analyzed by percentage techniques. The results of observations on the initial conditions indicate that children's scientific abilities are still low. The implementation of the first cycle of the first meeting until the third meeting showed an increase in children's scientific abilities, but had not been able to reach the KKM so the second cycle was carried out. After the second cycle, the first meeting until the third meeting shows a significant increase in children's scientific abilities, especially in the aspect of children, can practice how to cook from the ingredients to be used. Based on these studies it can be concluded that there is an increase in children's scientific abilities through experimental methods about sago flour in Pertiwi kajai Kindergarten, West Pasaman.